Analisis Frasa Idiomatik dalam Lirik Lagu “Dalam Diam” Karya Sal Priadi - Dewi, Sagita Tiara; Haryadi (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
Idiomatic phrases play a crucial role in enriching Indonesian language expression, particularly in verbal art forms such as modern song lyrics. This research aims to identify idiomatic phrases in the song "Dalam Diam" by Sal Priadi, analyze their structural formation, and describe their idiomatic meanings. This descriptive qualitative research employs observation and note-taking methods for data collection, and distributional analysis for examining data from the "Berhati" album (2020). Research findings identify six idiomatic phrases from the total comprehensive data discovered in the song lyrics, featuring diverse structures with dominant Noun + Verb + Noun (N+V+N) patterns. Idiomatic phrases are classified into six semantic categories: body and emotion metaphors, abstract personification, visual metaphors, light metaphors, nature metaphors, and sound and atmosphere metaphors. All categories contribute to conveying themes of introspection and self-contemplation. The research concludes that idiomatic phrases enhance the artistic dimension of contemporary Indonesian indie pop music and reflect modern Indonesian societal values in expressing emotional experiences through figurative language rich in symbolic meaning.